Contribution to the knowledge of five genres of the Familian Nitschkiaceae (Hymenoascomycetes: Sordariales) - San Martin Gonzalez, Felipe (Instituto de Ecología, A.C., 1996)
Brief comments on the taxonomic position of Nitschkiaceae of the Sordariales (= Coronophorales) are given. A key and descriptions for Calyculosphaeria, Fracchiaea, Scortechinia, Spinulosphaeria, and Thaxteria are provided. Calyculosphaeria calyculus (Mont.) Fitzp., C. tetraspora (Nannf.) comb. nov., Fracchiaea heterogena Sacc., Scortechinia acanthostroma Sacc. et. Berl., Spinulosphaeria thaxteri (Pat.) Sivanesan, and Thaxteria didyma (Speg.) Sacc. are described. The species were found associated with overmature pyrenomycetous stromata or growing on remains of tropical plants of Chiapas, Quintana Roo, Tamaulipas, and Veracruz